2019
DOI: 10.1210/js.2019-sat-571
|View full text |Cite
|
Sign up to set email alerts
|

SAT-571 Restoration of Thyroid Hormone Receptor Beta Signaling Reprograms Anaplastic Thyroid Cancer Cells

Abstract: Anaplastic thyroid cancer (ATC) is among the most lethal human cancers, with an average survival time of six months. These tumors are characterized by rapid local extension, resistance to radioactive iodine therapy and mainstream chemotherapy, and distant metastasis. There are very limited treatment options for this aggressive form of thyroid cancer, highlighting a need for a deeper understanding of its mechanisms for development of new targeted therapies. Loss of expression of the thyroid hormone receptor bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The importance of both TRβ1 and Runx2 has been investigated in several forms of cancer, including breast and thyroid cancer. In these cancers, TRβ1 has been considered to function as a tumor suppressor, and Runx2 as an oncogene [ 39 , 41 ]. Several investigations have shown that overexpression of TRβ1 reduces tumor growth, invasion, and metastasis in thyroid cancer [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of both TRβ1 and Runx2 has been investigated in several forms of cancer, including breast and thyroid cancer. In these cancers, TRβ1 has been considered to function as a tumor suppressor, and Runx2 as an oncogene [ 39 , 41 ]. Several investigations have shown that overexpression of TRβ1 reduces tumor growth, invasion, and metastasis in thyroid cancer [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%